Interperiod Correlation Model for Mexican Interface Earthquakes. Issue 3 (August 2019) - Jaimes, Miguel A.; Candia, Gabriel
This article presents a correlation model for pseudo-acceleration, peak ground acceleration, and peak ground velocity residuals using a database of Mexican subduction interface earthquakes at rock sites (NEHRP Class B). A mixed-effect regression model, a ground motion model, and 40 event recordings (418 records) with moment magnitude between five and eight were used to develop a magnitude-independent correlation model. This region-specific model yields consistently higher correlation values compared with similar studies developed for shallow crustal regions and other subduction zones worldwide, particularly for pseudo-acceleration values at distant periods. These results support the idea of using a region-specific and mechanism-specific correlation model for Mexico's subduction zone.